Method for predicting electromagnetic shielding performance of electronic equipment with micro-gap structure under corrosion condition

By constructing an equivalent conductivity calculation model and simulating corrosion conditions, measuring the transfer impedance and fitting the performance prediction model, the problem of difficult prediction of electromagnetic shielding performance in micro-slit structures in corrosion environments is solved, and the electromagnetic shielding performance degradation of shielded boxes is achieved accurate prediction.

CN119471118AActive Publication Date: 2025-02-18CHINA AERO POLYTECH ESTAB +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411593505.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

In a corrosive environment, the electromagnetic shielding performance of the micro-slit structure is difficult to accurately predict, resulting in complex electromagnetic leakage analysis of shielded boxes.

Method used

By constructing a calculation model of equivalent conductivity, the corrosion conditions are simulated to corrode the gap structure samples, the transfer impedance is measured, and the data fitting performance prediction model is used to predict the degradation of the electromagnetic shielding performance of the shielded box.

Benefits of technology

It quickly evaluates the electrical contact status of the microstructure surface of the shielded box under corrosion environment, and approximates the degradation of electromagnetic shielding performance, providing an important basis for product design and life evaluation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119471118A_ABST
    Figure CN119471118A_ABST
Patent Text Reader

Abstract

The invention discloses a method for predicting the electromagnetic shielding performance of electronic equipment with a micro-gap structure under a corrosion condition, and belongs to the field of electronic equipment electromagnetic shielding performance prediction.The method comprises the following steps that S1, a calculation formula of equivalent conductivity is constructed; s2, constructing a shielding box body with a micro gap structure and a plurality of groups of gap structure samples; and S3, simulating corrosion conditions, corroding the plurality of groups of gap structure samples, and collecting experimental data. And S4, calculating the equivalent conductivity based on the equivalent conductivity calculation formula constructed in the step S1, and predicting the electromagnetic shielding performance of the electronic equipment. According to the method, the conductivity parameter of the shielding body micro gap structure can be calculated, the surface electric contact state of the shielding box body micro structure in the corrosion environment can be rapidly evaluated, meanwhile, the electromagnetic shielding effectiveness degradation condition of the shielding box body can be further approximately evaluated, and an important basis and means are provided for accurate evaluation of the service life of the shielding body.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of prediction of electromagnetic shielding performance of electronic equipment, and in particular relates to a method for predicting electromagnetic shielding performance of electronic equipment with a tiny gap structure under corrosion conditions. Background Art

[0002] In a corrosive environment, changes in the electrical contact state of the surface structures such as the riveted gaps of the chassis or shielding body and the overlapped surface of the gasket are the main factors affecting the shielding effectiveness of the box. This gap structure and microstructure are corrosion-sensitive structures of the shielding body. From a microscopic point of view, considering the roughness of the contact surface, the microstructure of the overlapped gap is essentially an irregular array of holes. The degree of electromagnetic field leakage depends on the hole array formed by the physical contact surface and the properties of the added conductive gasket. The properties of the physical contact surface and the gasket vary due to the characteristics of the contact edge of the electronic equipment, the type of gasket, the pressure on the gasket, and the spacing of the screw installation. Most of these parameters cannot be accurately obtained. Moreover, the overall effect of the interaction between these parameters will make the electrical contact state of the surface of microstructures such as gaps more complicated. The further changes in the surface state of the micro-gap structure in a corrosive environment further increase the difficulty of electromagnetic leakage analysis of the shielding box.

[0003] To summarize the relevant research results at home and abroad, at present, most of the tests have been conducted by testing the transfer impedance of the gap filling material to analyze the electromagnetic shielding performance of shielding boxes with such tiny gap structures, such as electronic equipment. The fixture for testing the transfer impedance has strict requirements on the shape and size of the gap structure samples, which is significantly different from the actual installation status of the tiny gap structure on the shielding box.

[0004] In summary, it is urgent to study a method for calculating the electrical parameters of tiny gap structures under corrosion conditions, which can calculate the structural electrical parameters of tiny gaps and further predict the degradation of the electromagnetic shielding effectiveness of the shielding box. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides a method for predicting the electromagnetic shielding performance of electronic equipment with tiny gap structures under corrosive conditions. The method can quickly evaluate the electrical contact state of the surface of the tiny structure of the shielding box under a corrosive environment, and can further approximately evaluate the degradation of the electromagnetic shielding effectiveness of the shielding box, i.e., the electronic equipment. The method can propose positive design measures for product developers in the shielding body design stage, and provide important basis and means for the accurate evaluation of the service life of the shielding body.

[0006] To achieve the above object, the present invention discloses the following technical solution:

[0007] Specifically, the present invention provides a method for predicting the electromagnetic shielding performance of electronic equipment with a small gap structure under corrosion conditions, which comprises the following steps:

[0008] S1. The calculation model of equivalent conductivity is constructed as follows:

[0009]

[0010] Wherein, σ2 is equivalent conductivity; f is frequency; μ is magnetic permeability; h1 is the width of the actual micro-gap structure; h2 is the width of the equivalent micro-gap structure; n is a constant, which indicates the multiple of the depth of the conductor through which the current flows and the trend depth; Z T1 To measure the transfer impedance of small gap structures;

[0011] S2. Build a shielding box with a tiny gap structure and multiple groups of gap structure samples, each group of gap structure samples includes at least three gap structure samples;

[0012] S3, simulating corrosion conditions, corroding multiple groups of gap structure samples, and collecting experimental data to obtain the measured transfer impedance of the small gap structure, which specifically includes the following sub-steps:

[0013] S31, simulating corrosion conditions, corroding multiple groups of gap structure samples, specifically including:

[0014] S311, prepare an acidic salt solution for the test: prepare a NaCl solution and stir to dissolve the NaCl, then add a glacial acetic acid solution and stir again, measure the pH value of the solution after it reaches 3.0 to 3.1, let it stand for a period of time and measure the pH value of the solution again, and adjust the pH value of the solution to a constant value of 3.0 according to the measurement result;

[0015] S312, turn on the power of the salt spray test chamber, set the temperature of the salt spray test chamber to 30±5°C, set the temperature of the saturated barrel to 40±5°C, add water to the test chamber and the saturated barrel, and then add the NaCl solution with a pH of 3.0 prepared in step S311 into the salt spray test chamber;

[0016] S313, put multiple groups of gap structure samples into the salt spray test box in turn, inject clean water into the sealed water tank on the top of the salt spray test box, seal it and supply air to the salt spray test box, and at the same time adjust the air filter pressure on the back of the salt spray test box to 1.5±0.1kg, then turn on the spray switch and adjust the spray pressure value to 1.0±0.1kg, and start the test; during the test, set a certain time interval for sampling and testing, and perform sampling and testing after a certain time interval for each corrosion;

[0017] S314, after taking out a group of gap structure samples, measure and record the transfer impedance, and put the remaining gap structure samples back into the salt spray test chamber for the next time interval corrosion test;

[0018] S32, data collection and processing: taking the average value of the transfer impedances of multiple samples of each group of gap structure samples as the measured transfer impedance of the micro-gap structure;

[0019] S4, using the equivalent conductivity calculation model constructed in step S1 to calculate the equivalent conductivity and predict the electromagnetic shielding performance of the electronic equipment, the specific steps are:

[0020] S41, obtaining the transfer impedance of the measured micro-gap structure at different corrosion degrees during the corrosion test and calculating multiple groups of equivalent conductivities;

[0021] S42, plotting multiple groups of equivalent conductivity parameters as regular curves, fitting the data to obtain a performance prediction model of conductivity degradation with corrosion time, and judging the trend of shielding effectiveness degradation due to performance degradation of the tiny gap structure of the shielding box. If the decrease in equivalent conductivity exceeds 50% of the initial value, the shielding function of the shielding box is judged to be invalid. The performance prediction model is obtained by fitting the data based on the exponential form, and the expression is:

[0022] y=71.734e -0.024x

[0023] In the formula, y is the equivalent conductivity, and x is the corrosion time;

[0024] Alternatively, multiple groups of equivalent conductivity parameters are input into the simulation model to predict the shielding performance of the shielding box.

[0025] Preferably, in step S312, when the power is turned on for the first time, if the test low water level light and the saturated barrel low water level light on the test box operation panel are on, add an appropriate amount of clean water to the laboratory of the test box until the test low water level light goes out, and add clean water through the manual water inlet of the saturated barrel until the low water level indicator light of the saturated barrel goes out.

[0026] Preferably, in step S313, when sampling and testing are performed after a certain time interval of each corrosion, the sample should be cooled naturally to room temperature, and then the sample should be taken out and the deposited salt on the surface of the sample should be rinsed with water. Then, it should be further rinsed with distilled water, and the moisture on the surface of the sample should be blown away with dry compressed air. Finally, it should be placed for a certain period of time for natural drying.

[0027] Preferably, in step S313, the natural drying time is 24 hours, 36 hours or 48 hours.

[0028] Preferably, the shielding box equivalent micro-gap structure includes a first insulating block, a second insulating block and a contact structure simulation area, the first insulating block, the second insulating block and the contact structure simulation area are fixed together by means of fastening bolts, a non-conductive sealing gasket is arranged between the first insulating block and the fastening bolts, the contact structure simulation area includes a first metal clip, a second metal clip and a test gasket, and the test gasket is arranged between the first metal clip and the second metal clip.

[0029] Preferably, in step S42, the specific steps of inputting multiple groups of equivalent conductivity parameters into the simulation model to predict the shielding performance of the shielding box are as follows:

[0030] S421. Construct a simulation box model according to the actual size of the test, and set geometric parameters, including the length, width, height and thickness of the shielding box. The length and width of the shielding box are the same as the external length and width of the equivalent micro-gap, and the thickness of the shielding box is the difference between the inner length and the outer length of the equivalent micro-gap.

[0031] S422, drawing a geometric model, completing the simulation excitation source setting and boundary condition setting;

[0032] S423, completing the grid division setting, by meshing the equivalent gap structure, setting the maximum size of the grid so that 3-5 grids are included in the width direction of the small gap;

[0033] S424, completing the field monitor setting, setting the field monitoring point at the geometric center of the shielding box, and setting the solver at the same time;

[0034] S425, importing multiple sets of equivalent conductivity data into the equivalent gap structure, setting the model simulation frequency, and setting the frequency sweep mode to logarithmic sweep, the upper limit frequency and the lower limit frequency are designated as the lowest frequency point and the highest frequency point of the simulation, and the total number of frequency points is designated as the total number of frequency points of the simulation;

[0035] S426. Based on the above steps, the electric field strength and magnetic field strength inside the shielding box under different equivalent conductivities are solved, and the box shielding effectiveness monitoring value is calculated and output according to the electric field strength and magnetic field strength values.

[0036] Preferably, the sampling and testing interval in step S313 is 8h, 16h, 24h, 32h or 48h.

[0037] Preferably, step S1 specifically includes the following sub-steps:

[0038] S11, build a shielding box model with a gap structure, the width of the gap structure is h, and the cross-sectional area is S;

[0039] S12. Assuming that width leakage is not considered, the impedance of the equivalent small gap structure of the shielding box can be expressed by the volume resistance in its width direction;

[0040] S13. Construct a calculation model for equivalent conductivity.

[0041] Preferably, the specific process of constructing the calculation model of equivalent conductivity is as follows:

[0042] The volume resistance expression of the equivalent small gap structure is:

[0043]

[0044] In the formula, h represents the gap width, S represents the gap area, ρ represents the resistivity, and σ represents the conductivity of the gap;

[0045] Assuming the actual gap width is h1, the transfer impedance obtained by the test is Z T1 The contact area, width, gap length and conductivity of the equivalent model are S2, h2, l2, σ2 respectively, and its body impedance is Z T2 , the body resistance is R2, and considering the skin depth under high frequency conditions:

[0046]

[0047] Make the equivalent small gap structure model and the actual small gap structure model have the same shielding effectiveness, Z T1 and Z T2 The equivalence relationship must be satisfied, that is

[0048]

[0049] Further deduction, the calculation formula of equivalent conductivity is as follows:

[0050]

[0051] Compared with the prior art, the present invention has the following beneficial effects:

[0052] (1) The method of the present invention can realize the calculation of the conductivity parameters of the tiny gap structure of the shielding body, can quickly evaluate the electrical contact state of the surface of the tiny structure of the shielding box under a corrosive environment, can further approximately evaluate the degradation of the electromagnetic shielding effectiveness of the shielding box, and can propose positive design measures for product developers in the shielding body design stage, providing important basis and means for the accurate evaluation of the service life of the shielding body.

[0053] (2) Compared with the traditional transfer impedance evaluation method, the present invention can more directly and approximately truly reflect the trend of decreased shielding effectiveness due to the degradation of the tiny gap structure in the shielding box under the corrosive environment.

[0054] (3) Compared with traditional experiments and testing methods, the present invention can provide more comprehensive feedback on the corrosion effect of the shielding box in the actual service environment. The conductivity parameters can more intuitively reflect the failure modes such as the corrosion of the tiny gap structure of the shielding body, the generation of non-conductive corrosion products or the hydrolysis and aging of the rubber material, which leads to a decrease in the current conductivity on the surface of the box and thus affects the shielding effectiveness.

[0055] (4) The method proposed in the present invention can provide product designers with reference data for product anti-corrosion design. The corrosion effect of tiny gap structures can be taken into consideration at the early stage of the development of electronic equipment with a shielding structure, providing technical support for product development and improvement. At the same time, it can save subsequent maintenance costs, increase product life, and extend product service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1 is a flow chart of the present invention;

[0057] Figure 2a-2c Schematic diagram of the equivalent small gap model of the shielding box of the present invention, wherein: Figure 2a This is a schematic diagram of the model of the tiny gap structure. Figure 2b Schematic diagram of the characterization of the width of a tiny gap structure. Figure 2c Schematic diagram for characterizing the cross-sectional area of ​​a tiny gap structure;

[0058] Figure 3 This is a schematic diagram of the equivalent small gap structure of the shielding box of the present invention;

[0059] Figure 4 Schematic diagram of transfer impedance of a micro-gap structure, i.e., a beryllium bronze metal gasket, in an embodiment of the present invention;

[0060] Figure 5 A schematic diagram of prediction of a performance prediction model in an embodiment of the present invention;

[0061] Figure 6 Schematic diagram of an equivalent simulation model of an equivalent small gap structure of a shielding box in an embodiment of the present invention;

[0062] Figure 7 This is a schematic diagram of an interface for importing simulation time-frequency variable data in an embodiment of the present invention;

[0063] Figure 8 It is a schematic diagram of the implementation of the corrosion test of the shielding effectiveness of the beryllium bronze metal gasket contact structure for 80 hours in an embodiment of the present invention;

[0064] Fig. 9 This is a cloud diagram of the simulated electric field intensity distribution of the beryllium bronze metal gasket contact structure in an embodiment of the present invention;

[0065] Fig.10This is a cloud diagram of the simulated magnetic field intensity distribution of the beryllium bronze metal gasket contact structure in an embodiment of the present invention;

[0066] Fig.11 This is a diagram showing the current distribution on the surface of a simulated shielding body of a beryllium bronze metal gasket contact structure in an embodiment of the present invention. DETAILED DESCRIPTION

[0067] The exemplary embodiments, features and aspects of the present invention will be described in detail below with reference to the accompanying drawings. The same reference numerals in the accompanying drawings represent elements with the same or similar functions. Although various aspects of the embodiments are shown in the accompanying drawings, the drawings are not necessarily drawn to scale unless otherwise specified.

[0068] The present invention provides a method for predicting the electromagnetic shielding performance of electronic equipment with a small gap structure under corrosion conditions. Figure 1 As shown, it includes the following steps:

[0069] S1. Construct a calculation model for equivalent conductivity. The specific steps are as follows:

[0070] S11. Build a shielding box model with a gap structure, where the width of the gap structure is h and the cross-sectional area is S.

[0071] S12. Assuming that width leakage is not considered, the impedance of the equivalent small gap structure of the shielding box can be expressed by the volume resistance in its width direction.

[0072] S13, the conductivity calculation process of the equivalent small gap structure model is as follows:

[0073] The volume resistance expression of the equivalent small gap structure is:

[0074]

[0075] In the formula, h represents the gap width, S represents the gap area, ρ represents the resistivity, and σ represents the conductivity of the gap;

[0076] Assuming the actual gap width is h1, the transfer impedance obtained by the test is Z T1 The contact area, width, gap length and conductivity of the equivalent model are S2, h2, l2, σ2 respectively, and its body impedance is Z T2 , the body resistance is R2, and considering the skin depth r under high frequency conditions:

[0077]

[0078] Make the equivalent small gap structure model and the actual small gap structure model have the same shielding effectiveness, Z T1 and Z T2 The equivalence relationship must be satisfied, that is

[0079]

[0080] Further deduction, the calculation model of equivalent conductivity is as follows:

[0081]

[0082] Wherein, σ2 is equivalent conductivity; f is frequency; μ is magnetic permeability; h1 is the width of the actual micro-gap structure; h2 is the width of the equivalent micro-gap structure; n is a constant, which indicates the multiple of the depth of the conductor through which the current flows and the trend depth; Z T1 To measure the transfer impedance of the small gap structure.

[0083] S2. Build a shielding box with a tiny gap structure and multiple groups of gap structure samples to test the transfer impedance of the gap structure. Each group of gap structure samples includes 3 gap structure samples. A shielding box generally refers to an electronic device with a shielding function.

[0084] Specifically, Figure 3 As shown, the gap structure includes a first insulating block 1, a second insulating block 2 and a contact structure simulation area 3, the first insulating block 1, the second insulating block 2 and the contact structure simulation area 3 are fixed together by means of fastening bolts 4, a non-conductive sealing gasket 5 is arranged between the first insulating block 1 and the fastening bolts 4, the contact structure simulation area 3 includes a first metal clip 6, a second metal clip 7 and a test gasket 8, and the test gasket 8 is arranged between the first metal clip and the second metal clip.

[0085] S3, simulating corrosion conditions, corroding the crevice structure sample, and collecting experimental data, specifically including the following sub-steps:

[0086] S31. Simulate corrosion conditions to corrode the crevice structure sample, specifically including:

[0087] S311. Prepare an acidic salt solution for the test: prepare a 5% mass concentration NaCl solution and stir it thoroughly to completely dissolve the NaCl. Then, add glacial acetic acid solution to adjust the pH value of the solution. Stir it thoroughly again and measure the pH value to reach 3.0-3.1. After standing for 30 minutes, measure the pH value of the solution again. Make fine adjustments based on the measurement results to keep the pH value of the test solution constant at 3.0.

[0088] S312, turn on the power of the salt spray test chamber, set the test chamber temperature to 35±5℃, set the saturated barrel temperature to 45±5℃, add water to the test chamber and the saturated barrel, and add the pre-prepared NaCl solution with pH=3.0 and mass concentration of 5% into the brine reserve tank.

[0089] In step S312, when the power is turned on for the first time, if the test low water level light and the saturated barrel low water level indicator light on the test box operation panel are on, add an appropriate amount of clean water to the laboratory of the test box until the laboratory low water level indicator light on the operation panel goes out, and add clean water through the saturated barrel manual water inlet until the saturated barrel low water level indicator light goes out.

[0090] S313, put the samples into the salt spray test box and ensure that there is no shielding between the samples, inject clean water into the sealed water tank on the top of the test box, seal it and supply air to the test box, and adjust the air filter pressure on the back of the test box to 1.5±5kg, then turn on the spray switch and adjust the spray pressure value on the front panel to 1.0±5kg, and start the meter test; during the test, set a certain time interval between sampling and testing, and perform sampling and testing after a certain time interval of each corrosion. In a specific embodiment, the sampling and testing interval is set to 8h, 16h, 24h, 32h or 48h.

[0091] In step S313, when sampling and testing are performed after a certain time interval of each corrosion, the sample should be cooled naturally to room temperature. First, take out the sample and rinse it with tap water for 5 minutes to rinse the deposited salt on the surface of the sample. Then, rinse it further with distilled water and blow off the moisture on the surface of the sample with dry compressed air. Secondly, place it for a certain period of time to dry naturally. The natural drying time is 24h, 36h or 48h.

[0092] S314. After taking out the samples, a transfer impedance test system is set up to measure and record the samples, retain a group of samples, and put the remaining samples back into the test box for the next time interval corrosion test;

[0093] S32. Data collection and processing: The transfer impedance parameters of every three samples at different corrosion degrees are averaged as the measured transfer impedance of the micro-gap structure.

[0094] S4, calculating the equivalent conductivity based on the calculation formula of the equivalent conductivity constructed in step S1 and predicting the electromagnetic shielding performance of the electronic equipment, specifically:

[0095] S41. Obtain the transfer impedance of the measured tiny gap structure at different corrosion degrees during the corrosion test and calculate multiple groups of equivalent conductivities.

[0096] S42. Multiple groups of equivalent conductivity parameters are plotted as regular curves, and the performance prediction model of conductivity degradation with corrosion time is fitted to determine the trend of shielding effectiveness degradation due to the degradation of performance of the tiny gap structure. If the conductivity decreases by more than 50% of the initial value, the shielding function of the shielding box is judged to be invalid. The performance prediction model generally performs data fitting in an exponential form, and gives a fitting formula and R2 value. If the R2 value is greater than 0.9, it proves that the goodness of fit is good.

[0097] In an embodiment of the present invention, the expression of the performance prediction model is:

[0098] y=71.734e -0.024x

[0099] Where y is the equivalent conductivity and x is the corrosion time.

[0100] In this embodiment, data fitting is performed based on the degradation degree of the average conductivity test data results along with the test time, and the fitting results are as follows: Figure 5 As shown, the goodness of fit R 2 The value is greater than 0.9, and the fit is good. According to the conductivity test results, when the corrosion test was carried out for 48 hours, the average conductivity of the micro-gap structure dropped to 14.59S / m, and the drop value exceeded 80% of the initial value. It can be judged that the shielding effectiveness of the box will be greatly reduced due to the influence of corrosion on the micro-gap structure.

[0101] In other embodiments, step S42 predicts the shielding performance of the shielding box through simulation, and the specific steps are as follows:

[0102] Construct a simulation box model according to the actual size of the test, and set the geometric parameters, including the length, width, height and thickness of the shielding box. The length and width of the shielding box are the same as the external length and width of the equivalent point gap, and the thickness of the shielding box is the difference between the inner and outer lengths of the equivalent conductive gap.

[0103] Draw the geometric model, complete the simulation excitation source setting, in this embodiment, preferably set the uniform plane wave as the radiation excitation source. Set the boundary conditions, in this embodiment, preferably use the radiation boundary or FE-BI boundary.

[0104] Complete the mesh division setting, encrypt the mesh of the equivalent gap structure, set the maximum mesh size so that it contains 3-5 meshes in the gap width direction, and obtain higher simulation accuracy.

[0105] The field monitor setting is completed. In this embodiment, the field monitoring point is preferably set at the geometric center of the shielding box, and the complex mode values ​​of the electric field strength and the magnetic field strength are detected at the same time.

[0106] Complete the solver settings. In this embodiment, the preferred setting is 0.01 to meet the requirements.

[0107] After completing the above settings, import multiple sets of equivalent conductivity data into the equivalent gap structure; set the model simulation frequency, set the frequency sweep mode to logarithmic sweep, the upper and lower frequency limits specify the lowest and highest frequency points of the simulation, and the total number of frequency points specifies the total number of frequency points of the simulation.

[0108] Based on the above steps, the electric field strength and magnetic field strength inside the shielding box under different average equivalent conductivities are solved, and the box shielding effectiveness monitoring value is calculated and output according to the electric field strength and magnetic field strength values. Specific embodiments

[0110] The present invention provides a method for predicting electromagnetic shielding performance of electronic equipment with a small gap structure under corrosion conditions, and the specific implementation steps are as follows:

[0111] like Figure 2a-2c As shown in the figure, a shielding box is designed and developed according to the dimensions recommended in SAE ARP1173. The box is made of aluminum alloy, and the length, width and height are designed to be 305mm respectively. The panels around the shielding box are welded to the bottom plate, and a 2mm square groove is opened at the edge of the upper cover plate. The conductive rubber strip filled with glass-plated silver particles and silicone rubber is used to seal the panels around the box with aluminum alloy rivets.

[0112] According to the SAE ARP1705 C standard measurement fixture specimen size requirements, a "sandwich" structure gap structure simulation test piece is constructed. The metal clips on both sides of the "sandwich" structure are made of the same material as the shielding box, which is aluminum alloy. The test gasket is a beryllium bronze metal gasket. The outer diameter of the metal clip and the test gasket are both 20mm, the inner diameter is 16mm, and the wire diameter is 2mm. The appearance of the sample, i.e. the test piece, is as follows Figure 3 shown.

[0113] Then, the test was carried out in accordance with GB / T 10125-2021 Artificial atmosphere corrosion test salt spray test:

[0114] First, the acid salt solution used in the experiment was prepared and proportioned. 4000 mL of distilled water was measured with a measuring cylinder, and 200 g of pure NaCl was added. The NaCl content in the reagent was not less than 99.5%, and a 5% mass concentration NaCl solution was prepared, and the NaCl was fully stirred to completely dissolve.

[0115] Then, add glacial acetic acid solution to adjust the pH value of the solution, stir it again, measure the pH value until it reaches 3.0-3.1, let it stand for 30 minutes, measure the pH value of the solution again, and make fine adjustments based on the measurement results to ensure that the pH value of the test solution is constant at 3.0.

[0116] Secondly, turn on the power of the salt spray test chamber, set the chamber temperature to 35℃, and the saturated barrel temperature to 45℃. When powered on for the first time, the test low water level indicator and the saturated barrel low water level indicator on the test chamber operation panel will light up, indicating that there is a lack of water in these two places. Add an appropriate amount of clean water to the laboratory of the test chamber until the laboratory low water level indicator on the operation panel goes out, and add clean water through the manual water inlet of the saturated barrel until the saturated barrel low water level indicator goes out.

[0117] Next, add the pre-prepared NaCl solution with a pH of 3.0 and a mass concentration of 5% into the salt water reserve tank of the salt spray test chamber.

[0118] Finally, 15 test pieces, i.e., gap structure samples, are put into the box. Every 3 test pieces are used as a group of parallel samples to ensure that all test pieces are not blocked from each other. Pour clean water into the sealed water tank on the top of the test box, close the lid, and seal the test box. Turn on the air compressor to supply air to the test box. During this process, the air filter pressure on the back of the test box needs to be adjusted to 1.5kg, then turn on the spray switch, and adjust the spray pressure value on the front panel to 1.0kg to start the timing test.

[0119] During the test, when sampling and testing are carried out every 16 hours of corrosion, the samples should be cooled naturally to room temperature. First, take out all the test pieces and rinse them with tap water for 5 minutes to rinse off the deposited salt on the surface of the samples. Then, rinse further with distilled water and blow off the moisture on the surface of the samples with dry compressed air. Secondly, place them for 24 hours to dry naturally. Finally, set up a transfer impedance test system to measure and record the test pieces. After completing the above process, retain a group of test pieces (3 parallel samples), and put the remaining samples back into the test box for the next time interval corrosion test.

[0120] After the corrosion test, a total of 6 sets of data were obtained, including initial data, 16h, 32h, 48h, 64h, and 80h data. Figure 4 The specific data are shown in Table 1.

[0121] Simplifying other factors, assuming that the shielding box's tiny gap structure is a 2mm wide seam on the surface, the conductivity of the tiny gap structure can be calculated according to the following formula:

[0122]

[0123] Wherein, σ2 is equivalent conductivity; f is frequency; μ is magnetic permeability; h1 is the width of the actual micro-gap structure; h2 is the width of the equivalent micro-gap structure; n is a constant, which indicates the multiple of the depth of the conductor through which the current flows and the trend depth; Z T1 To measure the transfer impedance of the small gap structure.

[0124] Table 1

[0125] Duration of the test sample Test frequency range Average equivalent conductivity (S / m) 0h Beryllium Bronze Metal Gasket 10kHz–1.2GHz 91.91 16h Beryllium Bronze Metal Gasket 10kHz–1.2GHz 42.52 32h Beryllium Bronze Metal Gasket 10kHz–1.2GHz 37.85 48h Beryllium Bronze Metal Gasket 10kHz–1.2GHz 14.59 64h Beryllium Bronze Metal Gasket 10kHz–1.2GHz 14.70 80h Beryllium Bronze Metal Gasket 10kHz–1.2GHz 15.02

[0126] The conductivity degradation results of the tiny gap structure on the surface of the shielding box during the corrosion test are as follows:

[0127] According to the conductivity test results, when the corrosion test was carried out for 48 hours, the average conductivity of the micro-gap structure dropped to 14.59S / m, and the drop value exceeded 80% of the initial value. From this, it can be judged that the shielding effectiveness of the box will be greatly reduced due to the influence of corrosion on the micro-gap structure.

[0128] Simulation Example

[0129] A 3D simulation model of the shielding box is established based on the geometric dimensions and materials of the test shielding box, such as Figure 6 As shown. Taking the aviation aluminum shielding box as an example, the main body of the box is a cube with a side length of 310mm, a wall thickness of 10mm, and a cover plate with a side length of 380mm. By opening a square test window with a side length of 200mm on the front cover plate and matching it with a square test pressure plate with a side length of 260mm, the joint of the two square cover plates is the corrosion sensitive structure of the shielding box. In this simulation model, the green "annular belt" located between the two cover plates is a uniform and isotropic equivalent gap, and its width is h2, which is the distance between the contact surfaces of the two cover plates. In order to avoid the excessive fineness of the structural mesh division and the consumption of a large amount of computing resources due to the h2 value being too small during the solution process, h2 generally needs to be of the same order of magnitude as the thickness of the box.

[0130] Then use the import function in the parameter setting process to import the conductivity and assign an equivalent gap. Taking the HFSS simulation process as an example, the process of importing and assigning test data to the equivalent gap is as follows. First, open the material library interface, select the newly created material to which the equivalent gap is assigned. In this case, it is the material named "DUT". Click the Edit button to open its editing interface and the material property interface, in which you can set the various properties of the material. However, in this embodiment, the conductivity is frequency-variable, so you need to select the "Set Frequency Variation" button on the lower left to open the editing interface for setting the frequency-variable material, and select the "Enter points that vary with frequency" option in the sub-interface, enter the selection interface to select the material properties that need to be set to frequency-variable. In this article, only the frequency-variable setting of conductivity is involved. Set it, and the calculated frequency-variable test input import interface is as shown below. Figure 7 shown.

[0131] In the selection interface, you can also manually input the frequency-dependent conductivity in the input bar on the left. You can also use the import data button above to import the data into a data table in the ".dat" format. The results of the two imports are consistent. After importing the frequency-dependent data points, you can also observe the frequency-dependent law of the imported data in the drawing box on the right. After completing the above import work, confirm and save the settings to assign the frequency-dependent test data to the gap, and the data embedding is completed.

[0132] After embedding the test data in the simulation model, the solution conditions need to be set, including boundary conditions, excitation sources, and solution frequencies. In HFSS, the radiation boundary is embedded, which is suitable for electromagnetic shielding simulation. You only need to select the solution frequency to automatically divide the boundary. When simulating, the frequency for demarcating the boundary should be selected as the lower limit frequency. When simulating a frequency band with large changes, this will cause the grid density in the high-frequency range to be too large, which will cause the solution to fail. The appropriate solution frequency band is an upper limit frequency of 3 to 5 times the lower limit frequency. Beyond this range, it is recommended to use segmented solution, and then splice the simulation results.

[0133] For the setting of the excitation source, the "3m method" is followed. In the positive direction of the x-axis in the simulation model, a plane wave with an amplitude of 1V / m is set as the excitation source at a distance of 3m from the shield. The solution frequency is set according to actual needs, and is 10kHz to 1.2GHz in the present invention. The solution accuracy is set as required, and is set to 0.001 in the present invention, that is, the error between two iterations does not exceed 0.001, which can ensure good accuracy.

[0134] Finally, the electric field strength at the geometric center point of the shielding body is solved with and without the shielding body, and the shielding effectiveness of the shielding body is calculated based on this. According to the properties of plane waves, when there is no shielding, the electric field strength at the monitoring point is 1V / m, that is, 0dB. After the shielding body is installed, if the electric field strength at the monitoring point is X se dB, then the shielding effectiveness of the box is |X se |dB, which means that the shielding effectiveness equivalent simulation of the shielding body is completed.

[0135] After the corrosion test, the conductivity of the equivalent gap structure obtained from the test is substituted into the joint structure of the simulation model. Figure 8 This is a comparison curve of the measured and simulated values ​​of the shielding effectiveness of the box after 80 hours of degradation. The measured value and the simulated value are 52.59dB and 51.18dB respectively, with an error of 1.41dB.

[0136] like Figure 9-11As shown in the figure, it can be seen from the distribution of the electric field cloud map that the shield has well shielded the electric field, and the electric field peaks mainly appear at the edge of the shielding box cover and the seam of the cover, that is, the contact structure tested. This result shows that the electric field leaking into the shield is mainly caused by the electric field leakage of the box seam. It can be seen from the magnetic field distribution cloud map shown that the magnetic field is significantly weakened on the surface of the shield, and there is no obvious peak even at the gap. This is because the box is made of aluminum, which has a high magnetic permeability, and the gap is very narrow, and the air gap has a subtle effect. Therefore, the shield can form a closed magnetic circuit, guide the magnetic field to propagate on the surface of the shield without entering the inside of the shield, and obtain good magnetic field shielding effectiveness. By observing the surface current distribution shown, it can be seen that the surface current is consistent with the electric field distribution, mainly converging at the seam and the edge of the cover. The surface current gathered at the gap will cause a large voltage drop when flowing through the gap. According to relevant research, the voltage drop at the gap is equivalent to a new electromagnetic wave emission source, which will emit electromagnetic waves into the shield, resulting in a decrease in the electromagnetic shielding effectiveness of the shield. From the analysis of the cloud map distribution results, it can be seen that the seams of the shielding body are one of the main reasons for the decline in its shielding effectiveness. The corrosion and degradation of the seams will lead to a decrease in the electrical continuity of the seams and an increase in the transfer impedance, which will increase the ability of the gap to emit electromagnetic waves into the shielding box, causing a significant decline in shielding effectiveness.

[0137] The embodiments described above are only descriptions of the preferred implementation modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for predicting electromagnetic shielding performance of electronic equipment with a small gap structure under corrosion conditions, characterized in that: It includes the following steps: S1. The calculation model of equivalent conductivity is constructed as follows: Wherein, σ2 is equivalent conductivity; f is frequency; μ is magnetic permeability; h1 is the width of the actual micro-gap structure; h2 is the width of the equivalent micro-gap structure; n is a constant, which indicates the multiple of the depth of the conductor through which the current flows and the trend depth; Z T1 To measure the transfer impedance of small gap structures; S2. Build a shielding box with a tiny gap structure and multiple groups of gap structure samples, each group of gap structure samples includes at least three gap structure samples; S3, simulating corrosion conditions, corroding multiple groups of gap structure samples, and collecting experimental data to obtain the measured transfer impedance of the small gap structure, which specifically includes the following sub-steps: S31, simulating corrosion conditions, corroding multiple groups of gap structure samples, specifically including: S311, prepare an acidic salt solution for the test: prepare a NaCl solution and stir to dissolve the NaCl, then add a glacial acetic acid solution and stir again, measure the pH value of the solution after it reaches 3.0 to 3.1, let it stand for a period of time and measure the pH value of the solution again, and adjust the pH value of the solution to a constant value of 3.0 according to the measurement result; S312, turn on the power of the salt spray test chamber, set the temperature of the salt spray test chamber to 30±5°C, set the temperature of the saturated barrel to 40±5°C, add water to the test chamber and the saturated barrel, and then add the NaCl solution with a pH of 3.0 prepared in step S311 into the salt spray test chamber; S313, put multiple groups of gap structure samples into the salt spray test box in turn, inject clean water into the sealed water tank on the top of the salt spray test box, seal it and supply air to the salt spray test box, and at the same time adjust the air filter pressure on the back of the salt spray test box to 1.5±0.1kg, then turn on the spray switch and adjust the spray pressure value to 1.0±0.1kg, and start the test; during the test, set a certain time interval for sampling and testing, and perform sampling and testing after a certain time interval for each corrosion; S314, after taking out a group of gap structure samples, measure and record the transfer impedance, and put the remaining gap structure samples back into the salt spray test chamber for the next time interval corrosion test; S32, data collection and processing: taking the average value of the transfer impedances of multiple samples of each group of gap structure samples as the measured transfer impedance of the micro-gap structure; S4, using the equivalent conductivity calculation model constructed in step S1 to calculate the equivalent conductivity and predict the electromagnetic shielding performance of the electronic equipment, the specific steps are: S41, obtaining the transfer impedance of the measured micro-gap structure at different corrosion degrees during the corrosion test and calculating multiple groups of equivalent conductivities; S42, plotting multiple groups of equivalent conductivity parameters as regular curves, fitting the data to obtain a performance prediction model of conductivity degradation with corrosion time, and judging the trend of shielding effectiveness degradation due to performance degradation of the tiny gap structure of the shielding box. If the decrease in equivalent conductivity exceeds 50% of the initial value, the shielding function of the shielding box is judged to be invalid. The performance prediction model is obtained by fitting the data based on the exponential form, and the expression is: y=71.734e -0.024x In the formula, y is the equivalent conductivity, and x is the corrosion time; Alternatively, multiple groups of equivalent conductivity parameters are input into the simulation model to predict the shielding performance of the shielding box.

2. The method for predicting electromagnetic shielding performance of electronic equipment with a micro-gap structure under corrosion conditions according to claim 1 is characterized in that: In step S312, when the power is turned on for the first time, if the test low water level light and the saturated barrel low water level light on the test box operation panel are on, add an appropriate amount of clean water to the laboratory of the test box until the test low water level light goes out, and add clean water through the manual water inlet of the saturated barrel until the low water level indicator light of the saturated barrel goes out.

3. The method for predicting electromagnetic shielding performance of electronic equipment with a micro-gap structure under corrosion conditions according to claim 1, characterized in that: In step S313, when sampling and testing are performed after a certain time interval of each corrosion, the sample should be cooled naturally to room temperature. First, the sample should be taken out and the deposited salt on the surface of the sample should be rinsed with water. Then, it should be further rinsed with distilled water and the moisture on the surface of the sample should be blown away with dry compressed air. Finally, it should be placed for a certain period of time to dry naturally.

4. The method for predicting electromagnetic shielding performance of electronic equipment with a micro-gap structure under corrosion conditions according to claim 3 is characterized in that: In step S313, the natural drying time is 24 hours, 36 hours or 48 hours.

5. The method for predicting electromagnetic shielding performance of electronic equipment with a micro-gap structure under corrosion conditions according to claim 1, characterized in that: In step S311, the mass concentration of the NaCl solution is 5%, and the static period is 30 minutes.

6. The method for predicting electromagnetic shielding performance of electronic equipment with a micro-gap structure under corrosion conditions according to claim 1, characterized in that: The gap structure includes a first insulating block, a second insulating block and a contact structure simulation area, the first insulating block, the second insulating block and the contact structure simulation area are fixed together by means of fastening bolts, a non-conductive sealing gasket is arranged between the first insulating block and the fastening bolts, the contact structure simulation area includes a first metal clip, a second metal clip and a test gasket, and the test gasket is arranged between the first metal clip and the second metal clip.

7. The method for predicting electromagnetic shielding performance of electronic equipment with a micro-gap structure under corrosion conditions according to claim 1, characterized in that: The specific steps of inputting multiple groups of equivalent conductivity parameters into the simulation model to predict the shielding performance of the shielding box in step S42 are as follows: S421. Construct a simulation box model according to the actual size of the test, and set geometric parameters, including the length, width, height and thickness of the shielding box. The length and width of the shielding box are the same as the external length and width of the equivalent micro-gap, and the thickness of the shielding box is the difference between the inner length and the outer length of the equivalent micro-gap. S422, drawing a geometric model, completing the simulation excitation source setting and boundary condition setting; S423, completing the grid division setting, by meshing the equivalent gap structure, setting the maximum size of the grid so that 3-5 grids are included in the width direction of the small gap; S424, completing the field monitor setting, setting the field monitoring point at the geometric center of the shielding box, and setting the solver at the same time; S425, importing multiple sets of equivalent conductivity data into the equivalent gap structure, setting the model simulation frequency, and setting the frequency sweep mode to logarithmic sweep, the upper limit frequency and the lower limit frequency are designated as the lowest frequency point and the highest frequency point of the simulation, and the total number of frequency points is designated as the total number of frequency points of the simulation; S426. Based on the above steps, the electric field strength and magnetic field strength inside the shielding box under different equivalent conductivities are solved, and the box shielding effectiveness monitoring value is calculated and output according to the electric field strength and magnetic field strength values.

8. The method for predicting electromagnetic shielding performance of electronic equipment with a micro-gap structure under corrosion conditions according to claim 3, characterized in that: The sampling and testing interval in step S313 is 8h, 16h, 24h, 32h or 48h.

9. The method for predicting electromagnetic shielding performance of electronic equipment with a micro-gap structure under corrosion conditions according to claim 1, characterized in that: Step S1 specifically includes the following sub-steps: S11, build a shielding box model with a gap structure, the width of the gap structure is h, and the cross-sectional area is S; S12. Assuming that width leakage is not considered, the impedance of the equivalent small gap structure of the shielding box can be expressed by the volume resistance in its width direction; S13. Construct a calculation model for equivalent conductivity.

10. The method for predicting electromagnetic shielding performance of electronic equipment with a micro-gap structure under corrosion conditions according to claim 9, characterized in that: The specific process of constructing the calculation model of equivalent conductivity in step S13 is as follows: The volume resistance expression of the equivalent small gap structure is: In the formula, h represents the gap width, S represents the gap area, ρ represents the resistivity, and σ represents the conductivity of the gap; Assuming the actual gap width is h1, the transfer impedance obtained by the test is Z T1 The contact area, width, gap length and conductivity of the equivalent model are S2, h2, l2, σ2 respectively, and its body impedance is Z T2 , the body resistance is R2, and considering the skin depth under high frequency conditions: Make the equivalent small gap structure model and the actual small gap structure model have the same shielding effectiveness, Z T1 and Z T2 The equivalence relationship must be satisfied, that is Further deduction, the calculation model of equivalent conductivity is as follows:

Citation Information

Patent Citations

  • Electromagnetic shielding effect multi-field coupling simulation method for electronic device chassis with conductive rubber

    CN102004810A

  • Method for testing shielding effectiveness of electromagnetic shielding material

    CN103308798A

  • Transfer impedance-based miniature structural body shielding effectiveness test method

    CN108107290A

  • Method for evaluating shielding effectiveness of rectangular shielded cavity containing metal joint

    CN108414842A

  • Gap structure and electromagnetic shielding effectiveness evaluation method thereof

    CN110502863A